Art and the state the visual arts in comparative perspective - Alexander, Victoria D.; Rueschemeyer, Marilyn 1938- (St. Anthony's series, 2005)
"Two experts in the social study of the arts look at the impact of the nation-state - its actions, policies and traditions - on art institutions and artists. Focusing on the visual arts, the book examines cultural policy in the US, the UK, Norway, Sweden, and communist and postcommunist, eastern Germany Russian artists who emigrated to America and artists who experienced the transition in Germany give insight into contrasting political systems. Art and the State demonstrates that the art-state interaction is highly complex. The state has a degree of control, never absent and never absolute, over artists; artists in authoritarian societies carve out spaces of freedom, while artists in free-market countries submit to constraints imposed by the state, and by the marketplace. But the discussion goes far beyond the issues of autonomy and freedom. Other topics include the development of audiences, arts controversies, the privatization of arts institutions, and the public role of art and artists"--Book jacket.